Commissural malalignment on echocardiography as a predictor of coronary artery abnormalities in newborns with transposition of great arteries - Erkut Öztürk; Selman Gokalp; İbrahim Cansaran Tanıdır (Revista Portuguesa de Cardiologia)
Introduction and objectives: This study evaluated commissural malalignment on echocardiography as a predictor of coronary anomalies. Methods: All newborns diagnosed with transposition of great arteries in the pediatric cardiac intensive care unit between 1 August 2020 and 1 February 2022 were included in this study. The ratio of distances (C-ratio) from the anterior commissure to the right-sided commissure of the pulmonary valve and the distance from the anterior commissure to the left sided commissure of the pulmonary valve were calculated. According to the median effective level (EL50), it was classified as minor alignment or malalignment (C-ratio ≤EL50) or major malalignment (C-ratio >EL50). Preoperative classification results were compared with the intraoperative coronary anomalies defined by the surgeon. Results: A total of 60 cases were included in the study. Echocardiography revealed 16/38 (42%) commissural malalignment in the patient group with the usual coronary artery pattern and 15/22 (68%) in the patients with abnormal coronary artery patterns. The median commissural rotation angle was 28° (IQR 20–42). Although it was associated with the commissural malalignment (cut-off 30°, sensitivity 80% and specificity 85%, p=0.001), the commissural rotation angle was unrelated to the presence of a coronary artery anomaly. The C-ratio was 42% (0.42) according to the median effective level. Abnormal coronary artery pattern was more common in patients with major malalignment (C-ratio >0.42) (sensitivity 82% and specificity 88%, p=0.003). Conclusion: The incidence of coronary artery anomalies in patients with transposition of great arteries increases with major commissural malalignment. A high C-ratio might be a predictor of coronary artery anomaly. Resumo: Introdução e objetivos: Este estudo avaliou o mau alinhamento comissural na ecocardiografia como preditor de anomalias coronárias. Métodos: Todos os recém-nascidos diagnosticados com transposição das grandes artérias na unidade de cuidados intensivos cardíacos pediátricos entre 1 de agosto de 2020 e 1 de fevereiro de 2022 foram incluídos neste estudo. A razão de distâncias (razão C) da comissura anterior à comissura do lado direito da válvula pulmonar e a distância da comissura anterior à comissura do lado esquerdo da válvula pulmonar foram calculadas. De acordo com o nível eficaz mediano (EL50), foi classificado como alinhamento ou mau alinhamento menor (razão C ≤EL50) ou mau alinhamento maior (razão C >EL50). Os resultados da classificação pré-operatória foram comparados com as anomalias coronárias intraoperatórias definidas pelo cirurgião. Resultados: Foram incluídos no estudo 60 casos. A ecocardiografia revelou 16/38 (42%) maus alinhamentos comissurais no grupo de dontes com padrão de artéria coronária usual e 15/22 (68%) nos doentes com padrões de artéria coronária anormais. O ângulo de rotação comissural mediano foi de 28° (IQR 20-42). Embora estivesse associado ao mau alinhamento comissural (ponto de corte 30°, sensibilidade 80% e especificidade 85%, p=0,001), o ângulo de rotação comissural não estava relacionado com a presença de uma anomalia coronária. A razão C foi de 42% (0,42) de acordo com o nível eficaz mediano. O padrão de artéria coronária anormal foi mais comum em doentes com mau alinhamento maior (razão C >0,42) (Sensibilidade 82% e especificidade 88%, p=0,003). Conclusão: A incidência de anomalias das artérias coronárias em doentes com transposição das grandes artérias aumenta com o mau alinhamento comissural maior. Uma razão C alta pode ser um preditor de anomalia coronária.